Score, Rank, and Decision-Level Fusion Strategies of Multicode Electromyogram-Based Verification and Identification Biometrics - Pradhan, Ashirbad; He, Jiayuan; Jiang, Ning (IEEE journal of biomedical and health informatics, 2022)
Recent advances in biometric research have established surface electromyogram (sEMG) as a potential spoof-free solution to address some key limitations in current biometric traits. The nature of sEMG signals provide a unique dual-mode security: sEMGs have individual-specific characteristics (biometrics), and users can customize and change gestures just like passcodes. Such security also facilitates the use of code sequences (multicode) to further enhance the security. In this study, three levels of fusion, score, rank, and decision were investigated for two biometric applications, verification and identification. This study involved 24 subjects performing 16 hand/finger gestures, and code sequences with varying codelengths were generated. The performance of the verification and identification system was analyzed for varying codelength ( M : 1-6) and rank ( K : 1-4) to determine the best fusion scheme and desirable parameter values for a multicode sEMG biometric system. The results showed that the decision-level fusion scheme using a weighted majority voting resulted in an average equal error rate of 0.6% for the verification system when M = 4. For the identification system, the score-level fusion scheme with score normalization based on fitting a Weibull distribution resulted in a minimum false rejection rate of 0.01% and false acceptance rate of 4.7% using a combination of K = 2 and M = 4. The results also suggested that the parameters M and K could be adjusted based on the number of users in the database to facilitate optimal performance. In summary, a multicode sEMG biometric system was developed to provide improved dual-mode security based on the personalized codes and biometric traits of individuals, with the combination of enhanced security and flexibility.